Formation Graphs and Decentralized Formation Control of Multi Vehicles with Kinematics Constraints - Sisli, Ufuk Y.; Temeltas, Hakan (Springer Berlin Heidelberg, 2008)
In this work, decentralized formation control of a multi vehicle system is investigated. Each vehicle model considers kinematic constraints of differential drives which is a principal approach for various application for mobile robotics in 2D space. A virtual leader is assigned to navigate the whole cluster in a certain formation via predefined paths. Each vehicle produces its own control signal via communication with other vehicles and interactions with virtual leader. These interactions and communications are modeled with formation graphs. Formation graphs are widely used in multi vehicle decentralized formation control area. They provide a robust and scalable control approach and tools for designing stable systems.